2018
DOI: 10.1016/j.compag.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Classification of sheep urination events using accelerometers to aid improved measurements of livestock contributions to nitrous oxide emissions

Abstract: A. (2018). Classification of sheep urination events using accelerometers to aid improved measurements of livestock contributions to nitrous oxide emissions. Computers and Electronics in Agriculture, 150,[170][171][172][173][174][175][176][177]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 26 publications
0
25
1
Order By: Relevance
“…To date, most studies divided the multi-sensor data into segments using fixed-time segments [68][69][70] or a sliding sample window with a fixed length [38,71]. However, several studies testing the size of the window showed that it influences classification accuracy and the identification of short behaviours [53,[72][73][74]. Indeed, an individual can express both short and long behaviours, such as burst swimming in lemon sharks or a prey capture in Adélie penguins compared to normal swimming behaviour [37,75].…”
Section: Discussionmentioning
confidence: 99%
“…To date, most studies divided the multi-sensor data into segments using fixed-time segments [68][69][70] or a sliding sample window with a fixed length [38,71]. However, several studies testing the size of the window showed that it influences classification accuracy and the identification of short behaviours [53,[72][73][74]. Indeed, an individual can express both short and long behaviours, such as burst swimming in lemon sharks or a prey capture in Adélie penguins compared to normal swimming behaviour [37,75].…”
Section: Discussionmentioning
confidence: 99%
“…Published research using the same adhesive attachment mechanism used here demonstrated successful attachment for ca. 30 days 47 . Provided a VHF transponder is used, a ca.…”
Section: Discussionmentioning
confidence: 99%
“…Females often adopt a 'squat' posture when performing urine scent marks, but whether the signal produced in this posture could be discerned from a similar posture adopted when defecating has yet to be established. Scent marking has not yet been studied by concurrent use of GPS and accelerometers (see 47 for an example on livestock elimination events), but doing so may allow researchers to assign both time and location to scent mark observations, addressing the current methodological limitations identified above.…”
Section: A Novel Approach Using Biologging Techniquesmentioning
confidence: 99%
“…Important amounts of cow excreta on small areas may lead to localized releases of nitrogen into the soil. Identifying such areas could help to adapt management practices accordingly [ 6 ]. Finally, focusing on the relationship between ruminants and their environment is probably an interesting way to explore changes of behavior due to challenging situations [ 7 ].…”
Section: Introductionmentioning
confidence: 99%